ELECTROCEUTICALS: AN ALTERNATE BLESSING TO MANKIND - Srinivasan A; Amudha R; CRESENTA SHAKILA MOTHA L; Alamelu R; Nalini R (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The objective of the present study is to understand the use of electricity in treating ailments to mankind where they need not swallow the pills or inject intravenously rather have the device implanted which would monitor the nerve impulses, detect if any problems exist, and then supply electricity to the organs affected to make them function properly. This study is based on the case approach to identify the usefulness of electrical appliances for mankind. Each individual is unique and, therefore, electroceutical devices should also have the patient-specific element for smarter use of the implant. This newly emerging field of electroceuticals needs to be understood keeping in mind the body’s electrical grid and the language of nerve impulses to treat varied diseases and disorders affecting the mankind. The study pinpointed that electroceuticals is supplements to traditional treatment. Although much usefulness is found toward using electrical impulses to treat the organ, the devices need to be designed with relatively small wires and batteries for easier implantation. Each individual is unique and, therefore, electroceutical devices should also have the patient-specific element for smarter use of the implant. Keywords: Electroceuticals, Ailments, Electrical appliances, Patient-specific treatment.